Comparison of intravesical adjuvant therapy in bladder cancer with two different maintenance regimens of mitomycin and BCG. Issue 1 (February 2022) - Gupta, Sandeep; Dutta, Avisek; Pal, Dilip Kumar
Objective: To compare recurrence rate and side effects with two different maintenance regimens of postoperative intravesical therapy with mitomycin and BCG in T1 bladder cancer. Methods: Eighty were enrolled in this study and all received immediate post operative mitomycin. They were then allocated to two groups of 40, one group receiving intravesicle BCG and other a combination BCG and Mitomycin. They were followed up to a period of 2 years. Result: Two year recurrence rate after transurethral resection of bladder tumour with high grade T1 disease in the Combination group is low (20%) as compared to the BCG group (37.5%). Conclusion: Two year recurrences reduced with use of intravesical Mitomycin during maintenance in the combination group which though not statistically significant favours the trial with combination therapy in future studies. Side effect profile did not worsen with combination of Mitomycin and BCG.